2018
DOI: 10.1002/jia2.25096
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of HIV pre‐exposure prophylaxis in men who have sex with men and transgender women at high risk of HIV infection in Brazil

Abstract: IntroductionMen who have sex with men (MSM) and transgender women (TGW) in Brazil experience high rates of HIV infection. We examined the clinical and economic outcomes of implementing a pre‐exposure prophylaxis (PrEP) programme in these populations.MethodsWe used the Cost‐Effectiveness of Preventing AIDS Complications (CEPAC)‐International model of HIV prevention and treatment to evaluate two strategies: the current standard of care (SOC) in Brazil, including universal ART access (No PrEP strategy); and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“…As a result, transmission networks of resistance variants may have been selected among these MSM, thus reflecting this prevalence. Due to the higher prevalence of HIV infection in MSM (Kerr et al, 2018) and transgender women in Brazil (Grinsztejn et al, 2017), pre-exposure prophylaxis is recommended by the Brazilian Ministry of Health, who have made efforts to implement it and suggest it may be cost-effective (Luz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, transmission networks of resistance variants may have been selected among these MSM, thus reflecting this prevalence. Due to the higher prevalence of HIV infection in MSM (Kerr et al, 2018) and transgender women in Brazil (Grinsztejn et al, 2017), pre-exposure prophylaxis is recommended by the Brazilian Ministry of Health, who have made efforts to implement it and suggest it may be cost-effective (Luz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an analysis from Brazil found that PrEP provision to MSM/TGW at substantial risk (defined as any of the following behaviors in the prior 12 months: condomless anal sex with ≥2 partners, ≥2 episodes of anal sex with an HIV-infected partner, or history of STD diagnosis) would substantially reduce 5-year and lifetime risk of HIV infection [39]. In this analysis, PrEP adherence and uptake was assumed as per demonstration studies [40] and it was found that PrEP led to a cost per life-year saved that was well below Brazil's GDP per capita.…”
Section: Preventionmentioning
confidence: 99%
“…This initiative lead to a remarkable increase in PLWHA starting HAART in Brazil, from 48,696 to 81,177 in 2012 and 2015, respectively. Since 2015, 90% of patients receiving HAART in the country had been virally suppressed 6 . The efficacy of pre-exposure prophylaxis (PrEP) and its feasibility implementation in Brazil was recently demonstrated 6,7 and the strategy has been scheduled to be offered by the SUS from 2017 onwards, with some uneven outcomes due to ongoing budget restraints.…”
Section: Introductionmentioning
confidence: 99%